Pentadecanoic Acid, an Odd-Chain Fatty Acid, Suppresses the Stemness of MCF-7/SC Human Breast Cancer Stem-Like Cells through JAK2/STAT3 Signaling - To, Ngoc Bao; Nguyen, Yen Thi-Kim; Moon, Jeong Yong; Ediriweera, Meran Keshawa; Cho, Somi Kim (Nutrients, 2020)
Saturated fatty acids possess few health benefits compared to unsaturated fatty acids. However, increasing experimental evidence demonstrates the nutritionally beneficial role of odd-chain saturated fatty acids in human health. In this study, the anti-cancer effects of pentadecanoic acid were evaluated in human breast carcinoma MCF-7/stem-like cells (SC), a cell line with greater mobility, invasiveness, and cancer stem cell properties compared to the parental MCF-7 cells. Pentadecanoic acid exerted selective cytotoxic effects in MCF-7/SC compared to in the parental cells. Moreover, pentadecanoic acid reduced the stemness of MCF-7/SC and suppressed the migratory and invasive ability of MCF-7/SC as evidenced by the results of flow cytometry, a mammosphere formation assay, an aldehyde dehydrogenase activity assay, and Western blot experiments conducted to analyze the expression of cancer stem cell markers—CD44, β-catenin, MDR1, and MRP1—and epithelial–mesenchymal transition (EMT) markers—snail, slug, MMP9, and MMP2. In addition, pentadecanoic acid suppressed interleukin-6 (IL-6)-induced JAK2/STAT3 signaling, induced cell cycle arrest at the sub-G1 phase, and promoted caspase-dependent apoptosis in MCF-7/SC. These findings indicate that pentadecanoic acid can serve as a novel JAK2/STAT3 signaling inhibitor in breast cancer cells and suggest the beneficial effects of pentadecanoic acid-rich food intake during breast cancer treatments.